HAK ULAYAT SEBAGAI HAK KONSTITUSIONAL (Suatu Kajian Yuridis Empiris) - Agung Basuki Prasetyo (Masalah-Masalah Hukum, 2010)
Ulayat land is a beschikkingsrecht which describe about the relationships between indigenous people and their lands. Indigenous people say that there is a religio-magis character in that relationships. An empirical point of view can be described that ulayat rights still decrease on their recognization. It caused by conflicts, between indigenous people and government (vertical conflict) or between indigenous people and private corporation including inter indigenous people (horizontal conflict). In the framework to handle conflicts about ulayat lands, the government has an ambivalent attitude. In one side, the government give ulayat lands recognization and indigenous people's rights but in the other side, he deny indigenous people's rights. It urged by dirty political culture. As a matter of fact, there is an constitutional assurance of indigenous people's rights. It needed a long effort in order to get a constitutional recognization of indigenous people's rights not only in a paper but also in practice, it can be justification of law to protect ulayat lands of indigenous people